2020
DOI: 10.7759/cureus.11134
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Helicobacter Pylori Infection on Serology and Intestinal Mucosal Changes in Pediatric Patients With Celiac Disease: A Retrospective Cohort Study

Abstract: Introduction Helicobacter pylori (HP) and celiac disease (CD) can cause similar mucosal damage to the duodenal mucosa. For this reason, the relationship between these two diseases has been the subject of research recently. Our study aims to investigate the effects of HP infection on serology and pathology in pediatric patients with CD or potential celiac disease (PCD). Methods It is a retrospective cohort study conducted in the third-level education and research hospital between July 2017 and May 2019. The ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(33 reference statements)
1
1
0
Order By: Relevance
“…We evaluated the relationship between H. pylori infection and CD and found that H. pylori -positive CD patients demonstrated more severe mucosal damage than H. pylori -negative CD patients (Marsh grades 2 and 3) ( P = 0.018). This finding is similar to that of Gungor et al [ 40 ]. However, it has been reported that in individuals without CD, H. pylori infection itself can cause duodenal mucosal damage[ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…We evaluated the relationship between H. pylori infection and CD and found that H. pylori -positive CD patients demonstrated more severe mucosal damage than H. pylori -negative CD patients (Marsh grades 2 and 3) ( P = 0.018). This finding is similar to that of Gungor et al [ 40 ]. However, it has been reported that in individuals without CD, H. pylori infection itself can cause duodenal mucosal damage[ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…It is crucial to avoid misdiagnosis of PCD, either by overlooking another cause for TTG IgA elevation or by failing to diagnose CD. Transient TTG IgA elevation in the absence of CD has been described in giardiasis, 100 Helicobacter pylori infection, 101 liver disease, 102 inflammatory bowel disease, 103 autoimmune pancreatitis, 104 Graves disease 105 and fever 70 . Failure to identify histologic findings when present is a major contributor to underdiagnosis of CD and may arise from patient, clinician or laboratory factors.…”
Section: Potential Coeliac Diseasementioning
confidence: 99%